2007
DOI: 10.4028/www.scientific.net/amr.18-19.117
|View full text |Cite
|
Sign up to set email alerts
|

Management of Existing Capacity of Electric Power with Energy Saving Devices

Abstract: The strategy of management of the existing capacity by proper illumination design and the use of energy saving devices in the residential sector is reported. Improper installation design and the use of all sorts of devices at homes has led to a lot of electrical energy wastages resulting in the need to increase the generation capacity. The study revealed that annual energy of 551.88kWh could be saved for a three – bedroom flat when energy saving fluorescent lamps were used. The corresponding naira savings was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…In summary, this research finds that China's green investment and green ecology have a significant positive interaction mechanism from the level of dynamic relationship, influence mechanism, and regional heterogeneity. Our conclusion confirms the research conclusions of Shen et al [16], Ekeh, Wara, and Orovwode [11].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In summary, this research finds that China's green investment and green ecology have a significant positive interaction mechanism from the level of dynamic relationship, influence mechanism, and regional heterogeneity. Our conclusion confirms the research conclusions of Shen et al [16], Ekeh, Wara, and Orovwode [11].…”
Section: Discussionsupporting
confidence: 93%
“…In terms of GE, Ekeh, Wara, and Orovwode [11] indicated that green finance is effective for economic greening and low-carbon development. Labatt [19] indicated that green finance provides the foundation for the development of the GE and provides the possibility for sustainable development; Wang and Wang [20] argued that green finance has different effects on inclusive economic growth in different regions and has a great impact on the central and western regions.…”
Section: Green Investment Promotes Green Ecological Developmentmentioning
confidence: 99%
See 2 more Smart Citations